Hypophysitis Caused by Ipilimumab in Cancer Patients: Hormone Replacement or Immunosuppressive Therapy - Lammert, A.; Schneider, H. J.; Bergmann, T.; Benck, U.; Krämer, B. K.; Gärtner, R.; Metzner, C.; Schöfl, C.; Berking, C. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Ipilimumab is besides the BRAF inhibitor vemurafenib the first officially approved medical treatment for metastatic melanoma, which results in improved survival. Ipilimumab leads to a release of a CTLA4-mediated inhibition of T-cell immunoreactions. Therefore, patients may also suffer from immune-related adverse events affecting different organs, which are typically treated by high-dose corticosteroids. Ipilimumab-induced hypophysitis (iH) has been reported in up to 17% of melanoma patients in clinical trials.Here we present 5 patients with metastatic melanoma and 2 patients with prostate cancer who developed hypophysitis after ipilimumab therapy. Patients were treated by high-dose corticosteroid therapy resulting in the resolution of local inflammation but not of pituitary deficiencies. Partial or complete hypopituitarism remained in all patients. Pharmacotherapy with high-dose corticosteroids caused complications in 5 patients, necessitating hospitalization in 4. 2 of the 3 patients with progressive disease died, while 3 patients had stable disease and 1 patient showed tumor regression after discontinuation of ipilimumab.In summary, with regard to safety and simplicity of hormonal substitution therapy we have to scrutinize high-dose corticosteroid therapy, though it only improves inflammation but not neuro-endocrine function and may cause further morbidity. Regression of the tumor depends on the ipilimumab-mediated immune events, in which high-dose and long-term corticosteroid therapy for iH appears to be counter-intuitive. Herein, we discuss screening and the diagnostic as well as therapeutic management of iH in metastatic cancer patients from an endocrinologic perspective.
Keywords: autoimmunity; hypopituitarism; glucocorticoids